Exploring the Pharmacological Potential of Metformin for Neurodegenerative Diseases - Du, Ming-Rui; Gao, Quan-You; Liu, Chen-Lin; Bai, Lin-Ya; Li, Tian; Wei, Fei-Long (Frontiers in Aging Neuroscience, 2022)
Metformin, one of the first-line of hypoglycemic drugs, has cardioprotective, anti-inflammatory and anticancer activities, in addition to its proven hypoglycemic effects. Furthermore, the preventive and therapeutic potential of metformin for neurodegenerative diseases has become a topic of concern. Increasing research suggests that metformin can prevent the progression of neurodegenerative diseases. In recent years, many studies have investigated the neuroprotective effect of metformin in the treatment of neurodegenerative diseases. It has been revealed that metformin can play a neuroprotective role by regulating energy metabolism, oxidative stress, inflammatory response and protein deposition of cells, and avoiding neuronal dysfunction and neuronal death. On the contrary, some have hypothesized that metformin has a two-sided effect which may accelerate the progression of neurodegenerative diseases. In this review, the results of animal experiments and clinical studies are reviewed to discuss the application prospects of metformin in neurodegenerative diseases.